Social innovations as opportunities: how can innovations in social services be stimulated and managed? - Eurich, Johannes; Langer, Andreas (Diaconia, 2016)
Pending challenges like demographic changes require new solutions in social welfare systems. This article focuses on innovations in the social field and presents the findings of the European research project Innoserv - Social Platform on Innovative Social Services. Innovation in social services is defined by the implementation and diffusion of new practices in four dimensions (object, time, social dimension, and sustainability). Based on this concept as well as on empirical findings, we identified seven innovation trends with regard to products, organizational processes and institutional frameworks. In light of these trends, the question is how innovations can be implemented into an organization through social management. Social innovations are often initiated by strategic alliances and need to be transferable, because they are bound to local contexts and rely on the help of external experts. Agents of change are decisive for promoting social innovations. The key task is to integrate all these actors into a (management) framework that allows for innovations to be developed.
Gesehen am 13.09.2017